Interactions between winter and summer herbivory affect spatial and temporal plant nutrient dynamics in tundra grassland communities. Issue 8 (18th May 2020) - Petit Bon, Matteo; Gunnarsdotter Inga, Katarina; Jónsdóttir, Ingibjörg Svala; Utsi, Tove Aagnes; Soininen, Eeva Marjatta; Bråthen, Kari Anne
Abstract : In the long‐term, herbivores can alter nutrient dynamics in terrestrial ecosystems by changing the functional composition of plant communities. Here, we ask to what extent herbivores can affect plant‐community nutrient dynamics in the short‐term. We provide theoretical expectations for immediate effects of herbivores on tundra‐grassland plant‐community nutrient levels throughout a single growing season and empirically evaluate these predictions. We established an experiment within two forb‐dominated and two grass‐dominated tundra‐grassland communities. We selected tundra‐patches disturbed by small rodents during the previous winter, and neighbouring undisturbed tundra‐patches. Within each tundra‐patch, we set up a reindeer‐open and a reindeer‐exclusion plot. Throughout the summer, we randomly collected over 2800 leaf samples from 34 vascular plant species/genera and analysed their nitrogen and phosphorus contents. Plant‐community nutrient levels were consistently higher in tundra‐patches affected by small rodents, both across tundra‐grassland types and throughout the growing season. Forbs and grasses growing in small‐rodent disturbed tundra‐patches had 11% and 25% higher nutrient content, respectively, compared to undisturbed tundra‐patches. Reindeer affected only grasses growing in grass‐dominated tundra‐grasslands and the outcome was dependent on small‐rodent winter disturbance. Reindeer increased grass nitrogen content in undisturbed tundra‐patches (+7%) and weakened the positive effects of small rodents in disturbed tundra‐patches (from 25% to 15% higher nutrient content [both nitrogen and phosphorus]). By enhancing plant nutrient levels throughout a single growing season, herbivores were key, immediate modifiers of plant‐community nutrient dynamics in tundra‐grasslands. Higher nutrient contents still detected in senescent leaves at the end of the summer in herbivore‐affected tundra suggest that herbivory is accelerating short‐term tundra‐grassland nutrient cycling rates. Our findings from tundra‐grassland communities align with theoretical expectations of positive herbivore effects on nutrient cycling in relatively productive ecosystems.